CLINICAL FEATURES AND CLINICAL OUTCOME OF ACUTE PROMYELOCYTIC LEUKEMIA PATIENTS TREATED AT CAIRO NATIONAL CANCER INSTITUTE IN EGYPT - Khorshid, Ola; Diaa, Amira; El Moaty, Mohamed Abd; El Fatah, Rafat Abd; El Dessouk, Ihab; El Hamid, Maha Abd; El Noshokaty, Essam; El Saied, Ghada; Fouad, Tamer M; Ramadan, Safaa M (Mediterranean Journal of Hematology and Infectious Diseases, 2011)
The current study reports the clinical features and treatment outcome of 67 patients with acute promyelocytic leukemia (APL) presented to National Cancer Institute (NCI-Cairo), in Egypt from January 2007 to January 2011. The median follow-up time was 36 months. All patients were treated with the simultaneous administration of all-trans retinoic acid (ATRA) and anthracyclin. The treatment protocol was modified due to resource limitations at the NCI-Cairo by replacing of idarubicin with doxorubicin in most of the cases and the inclusion of cytarbine during the consolidation phase only in pediatric patients. All patients who achieved molecular complete remission (CRm) after consolidation received two-year maintenance treatment with low dose chemotherapy composed of 6 mercaptopurine, methotrexate and intermittent ATRA courses. The median age at presentation was 29 years. There was a slight male predominance (53%). Bleeding was the most common presenting symptom (79%). Most patients had an intermediate risk Sanz score (49%) and 34% had a high risk score. All patients achieved molecular CR at end of consolidation therapy with a median duration of 100 days. The main therapeutic complications during the induction phase were febrile neutropenia (42%), bleeding (18%) and differentiation syndrome (11%). Five patients died at diagnosis due to bleeding, three died during induction chemotherapy due to febrile neutropenia (n=2) and bleeding (n=1) and one patient died during consolidation therapy due to febrile neutropenia. The 3-year OS was 89% and relapse rate was 3%. Adapting standard AIDA treatment protocols to limited resources by reducing dose-intensity during treatment consolidation, using ATRA in the consolidation phase and alternative anthracyclin (doxorubicin) may be a valid treatment option in developing countries. In spite of the increased incidence of high and intermediate risk score APL in our sample, we reported an acceptable CR rate, toxicity and OS.